2023
DOI: 10.1021/acsami.2c22519
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput Screening toward Efficient Nitrogen Fixation: Transition Metal Single-Atom Catalysts Anchored on an Emerging π–π Conjugated Graphitic Carbon Nitride (g-C10N3) Substrate with Dirac Dispersion

Abstract: TM-N x is becoming a comforting catalytic center for sustainable and green ammonia synthesis under ambient conditions, resulting in increasing interest in single-atom catalysts (SACs) for the electrochemical nitrogen reduction reaction (NRR). However, given the poor activity and unsatisfactory selectivity of existing catalysts, it remains a long-standing challenge to design efficient catalysts for nitrogen fixation. Currently, the two-dimensional (2D) graphitic carbon-nitride substrate provides abundant and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…1a, which possesses an intrinsic central cavity to stably anchor one TM and further exists in the form of SACs, realized by TM@g-C 10 N 3 . 18 We choose VIII group elements, including 3d TM (Fe, Co, and Ni), 4d TM (Ru, Rh, and Pd), and 5d TM (Os, Ir, and Pt) to anchor into g-C 10 N 3 to build SACs. We have considered two N-coordination environments, one where the TM is surrounded by two N atoms (red circle represents site I) and the other where the TM is surrounded by three N atoms (the green circle represents site II), as plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a, which possesses an intrinsic central cavity to stably anchor one TM and further exists in the form of SACs, realized by TM@g-C 10 N 3 . 18 We choose VIII group elements, including 3d TM (Fe, Co, and Ni), 4d TM (Ru, Rh, and Pd), and 5d TM (Os, Ir, and Pt) to anchor into g-C 10 N 3 to build SACs. We have considered two N-coordination environments, one where the TM is surrounded by two N atoms (red circle represents site I) and the other where the TM is surrounded by three N atoms (the green circle represents site II), as plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, Zhang et al have demonstrated that TM anchored into g-C 10 N 3 exhibits good stability, excellent conductivity, and high NRR catalytic activity. 18 Otherwise, a report shows that Re can be stably anchored into g-C 10 N 3 , offering a promising strategy for formation of SACs. 19 Therefore, based on these properties of g-C 10 N 3 , we predict that g-C 10 N 3 is likely to be a promising substrate to anchor TM atoms for the ORR/OER/HER.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we believe that this strategy can also be applied to screen SACs for Li─S and Na─S batteries supported by C x N y systems containing cavities (similar to g-C 3 N 4 ), such as C 2 N, [38] C 3 N 3 , [39] and C 10 N 3 . [40] For the screened MM@g-C 3 N 4 (including seven TM@g-C 3 N 4 and three MM@g-C 3 N 4 ), their ability to inhibit the shuttle effect was investigated. The anchoring capacity of the reaction intermediates on seven TM@g-C 3 N 4 was evaluated based on the adsorption energy, as shown in Figure 7a.…”
Section: Resultsmentioning
confidence: 99%
“…DLP = LP NRR À LP HER . 77,79 A positive deviation of DLP with respect to À0.5 V demonstrates a favorable NRR selectivity. The more positive the DLP value is, the higher the NRR selectivity of the TM@BNNCs.…”
Section: The Nrr Performance Of Tm@bnncsmentioning
confidence: 99%